Tanggung Jawab Hukum Perusahaan Teknologi Atas Penyalahgunaan Data Pengguna : Studi Kasus Di ASEAN - Idris, Maulana Fahmi; Laksito, Joni; Ariyani, Widya (Universitas Sains dan Teknologi Komputer, 2024)
This study examines the legal responsibility of technology companies in protecting user data in the ASEAN region amidst the increasing risks of data misuse in the digital era. The research adopts a qualitative approach, analyzing existing data protection regulations in Indonesia, Malaysia, and Hong Kong, and compares these to the General Data Protection Regulation (GDPR) in the European Union. The findings reveal significant regulatory disparities within ASEAN, with countries facing challenges in enforcement and public awareness regarding data privacy. Case studies of data breaches highlight the need for stronger security measures and transparency from technology companies to protect user data. Additionally, this study underscores the importance of regional collaboration among ASEAN countries to establish harmonized and effective data protection standards that align with global best practices. Strengthening data protection regulations and enforcement mechanisms can foster a safer digital environment, promoting user trust and supporting sustainable digital economic growth in the region.